Why is a picture 'worth a thousand words'? Pictures as information in perceived helpfulness of online reviews. (12th November 2020) - Wu, Ruijuan; Wu, Heng‐Hui; Wang, Cheng Lu
Abstract: The hybrid review format (verbal reviews accompanied by pictures) is increasingly prevalent in online consumer reviews. However, the mechanism behind the superiority effect of hybrid reviews is still unclear. Unlike previous studies based on information processing theory that emphasize the imagery‐provoking ability of the verbal information, we contend that imagery in hybrid reviews is the information that adds more diagnostic value to online reviews and thus makes the reviews more helpful. Our experimental studies found that hybrid reviews were perceived as more helpful than word‐only reviews, and this effect was explained by the perceived amount of information. Moreover, the superiority effect of hybrid reviews on perceived helpfulness was found to be contingent on the review extremity and viewing tasks. These results confirmed our hypothesis of picture as information, explaining the superiority effect of hybrid reviews and pinpointed the conditions under which such an effect would occur or disappear.